Upcycling of By-Products from Autochthonous Red Grapes and Commercial Apples as Ingredients in Baked Goods: A Comprehensive Study from Processing to Consumer Consumption - Gaetano Cardone; Martina Magni; Veronica Marin; Andrea Pichler; Daniele Zatelli; Peter Robatscher; Ombretta Polenghi; Virna Lucia Cerne; Michael Oberhuber; Silvano Ciani (Antioxidants)
Lagrein grape (Vitis vinifera L.) pomace and Scilate apple (Malus domestica Borkh.) skin are polyphenol- and antioxidant-rich by-products with promising applications in the food industry. This study investigated the impact of drying and grinding on their antioxidant properties for use in gluten-free baked goods. Regardless of the by-product analysis, the results showed that processing conditions effectively preserved most of the polyphenols. Furthermore, the grape pomace and apple skin flours produced retained approximately 86% and 66% of anthocyanins, respectively. Incorporating these flours into breadsticks, focaccia, and cookies significantly enhanced their polyphenol content (300–727%), anthocyanin content (600–1718%), and antioxidant capacity (280–1200%). The addition of these by-products to baked goods led to a slight decrease in texture and sensory properties. However, adding both grape pomace and apple skin flours significantly improved consumer acceptance compared to products containing only grape pomace flour. This study highlights the potential of upcycling by-products from grapes and apples to enhance the nutritional profile of gluten-free products while supporting a circular economy approach.